2020
DOI: 10.1074/jbc.ra120.015489
|View full text |Cite
|
Sign up to set email alerts
|

Leptin modulates pancreatic β-cell membrane potential through Src kinase–mediated phosphorylation of NMDA receptors

Abstract: The adipocyte-derived hormone leptin increases trafficking of KATP and Kv2.1 channels to the pancreatic β-cell surface, resulting in membrane hyperpolarization and suppression of insulin secretion. We have previously shown that this effect of leptin is mediated by the NMDA subtype of glutamate receptors (NMDARs). It does so by potentiating NMDAR activity, thus enhancing Ca2+ influx and the ensuing downstream signaling events that drive channel trafficking to the cell surface. However, the molecular mechanism b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 80 publications
1
23
0
Order By: Relevance
“…However, this effect of leptin was greatly attenuated by the presence of st-Ht31 indicating that blocking PKA from binding AKAPs prohibits leptin from increasing KATP channel surface density. Previously we have shown that the increased abundance of KATP channels in the membrane enhances total K + conductance and causes -cells to hyperpolarize [7][8][9][10] . To further verify the importance of PKA-AKAP interactions for KATP channel translocation we monitored the effects of st-Ht31 on cell membrane potential following leptin treatment using cell-attached current clamp recording, which is a non-invasive approach for detecting changes in membrane potential without disturbing cellular integrity or compromising intracellular soluble factors important for signaling 34,35 .…”
Section: Leptin Signaling Via Pka Requires Akapsmentioning
confidence: 98%
See 4 more Smart Citations
“…However, this effect of leptin was greatly attenuated by the presence of st-Ht31 indicating that blocking PKA from binding AKAPs prohibits leptin from increasing KATP channel surface density. Previously we have shown that the increased abundance of KATP channels in the membrane enhances total K + conductance and causes -cells to hyperpolarize [7][8][9][10] . To further verify the importance of PKA-AKAP interactions for KATP channel translocation we monitored the effects of st-Ht31 on cell membrane potential following leptin treatment using cell-attached current clamp recording, which is a non-invasive approach for detecting changes in membrane potential without disturbing cellular integrity or compromising intracellular soluble factors important for signaling 34,35 .…”
Section: Leptin Signaling Via Pka Requires Akapsmentioning
confidence: 98%
“…We have previously shown that leptin promotes trafficking of KATP channels to the plasma membrane, causing increased K + conductance and cell hyperpolarization in rat insulinoma INS-1 832/13 cells as well as primary mouse and human -cells [7][8][9][10] . Our prior work revealed that a critical event for this process is actin remodeling 7 , which presumably allows vesicles containing potassium channels to translocate and insert into the -cell membrane [26][27][28][29] .…”
Section: Leptin Increases Pka Activity Near the Plasma Membranementioning
confidence: 99%
See 3 more Smart Citations